Ancaman Keamanan Manusia: Sepak Terjang Taliban Menguasai Afghanistan - Hanindya Ratih Febriana (UIR Press, 2021)
The Taliban is a movement that originated from a group of madrasa students in Kandahar. The lack of concern for the plight of the Afghan people from the Mujahideen led to the emergence of this movement. The Mujahideen camp was only preoccupied with gaining power by fighting and constantly attacking each other. The formation of the Taliban movement had a positive goal, namely to fight corruption and improve security, but turned into a negative because they applied the harsh teachings of Islam in their own way and applied Islamic law which was brutal enough to cause human rights violations and forced women in Afghanistan to be bear the brunt of the Taliban regime. After the Taliban took control of Afghanistan, the only Sunni Islamic country that had a Shariah legal basis was Afghanistan. From these problems, of course the question will arise why and how the Taliban movement emerged in Afghanistan, then what is the impact of the Taliban movement in Afghan and how the Taliban movement can threaten the security of Afghan society.